Floating Nurseries as an Agronomic Technology for Improving Rice Production in Lebak Swamplands: A Structural Equation Modeling Approach - Eka Mulyana; Sriati Sriati; Muhammad Yamin; Yunita Yunita; Susilawati Susilawati; Agustina Bidarti (Universitas Panji Sakti, 2026)
Rice productivity in lowland rice fields is critical to feeding the national food estate and warrants researchers' attention. This paper investigates the impact of input provision, floating rice cultivation, local wisdom knowledge, and local wisdom strategy on the productivity of floating rice cultivation in lowland rice fields in Ogan Ilir, Indonesia. This study analyzes how institutional support and floating rice land typology influence input provision, floating rice cultivation, local wisdom knowledge, local wisdom strategy, and floating rice cultivation productivity. The researchers employed a survey questionnaire to gather primary data from selected participants. The researchers employed smart-PLS to examine the association between factors. Structural Equation Modeling (SEM) and field measurements were used to examine data from 250 farmers. The results of the research indicate that input provision, floating rice cultivation, local wisdom understanding, and local wisdom strategy all contribute to increased floating rice cultivation productivity. The findings show that institutional support has a substantial influence on the link between input provision, floating rice cultivation, local wisdom knowledge, local wisdom strategy, and floating rice cultivation productivity. This study advises policymakers on local and national policies to increase floating rice cultivation productivity by implementing efficient input provision, effective floating rice cultivation, local wisdom knowledge, and the use of long-term local wisdom strategies.